A Critical Study Of The Sodaqoh Tradition From The Perspective Of Character Education: A Phenomenological Study Of The Sunan Gunung Jati Burial Complex, Cirebon - Ditta Septiani Putri; Sabina Octavia Rachman; Annisa Putri Winarti; Iin Wariin Basyari; Iis Yeni Sugiarti (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of the sodaqoh tradition on the formation of the independence character of elementary school-age children involved in the practice of begging at the Sunan Gunung Jati Cemetery Complex, Cirebon. The sodaqoh tradition that has taken root in this society not only contains cultural and spiritual values, but also has the potential for negative impacts on the development of children's character, especially in terms of independence, morality, and ethical attitudes. The research uses a qualitative approach with phenomenological methods and a single case study. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation. The informants consisted of cultural experts, tomb managers, pilgrims, and children who were active in asking for sodaqoh, selected through purposive techniques and snowball sampling. The research instruments include interview guidelines, observation sheets, and documentation. Data were analyzed using a qualitative descriptive approach through the stages of data reduction, data presentation, and conclusion drawn, with validity tested through triangulation of sources and techniques. The results of the study show that the phenomenon of begging visitors/tourists is a tradition in the community in the Suanan Gunungjati Cirebon cemetery complex. From 3 case studies of elementary school-age children who are directly involved as shodaqoh requesters, it shows a lack of independent character among them.